Fiscal Federalism in the 21st Century - David R. Agrawal; Jan K. Brueckner; Marius Brülhart (Center for Economic Studies and ifo Institute (CESifo), 2024)
Fiscal federalism concerns the division of policy responsibilities among different levels of government. Many current economic and policy developments, such as globalization, environmental crises and rising inequality, may not appear to be favorable to fiscal federalism, yet countries are further decentralizing their fiscal systems. We summarize the efficiency and equity aspects fiscal decentralization, fiscal competition, fiscal externalities, and intergovernmental grants. The survey introduces readers to theoretical reasons for/against a federalist structure. We discuss how federalism relates to classic problems in economics: externalities, inequality, spillovers, information, and aspects of political economy. Our survey integrates both theory and empirics, while also focusing on the variety of federal systems in different countries, both developing and developed. We conclude by discussing how fiscal federalism is being shaped by economic, technological, and environmental changes, while discussing the effects of globalization, polarization, and global crises on the future of federal systems.
Keywords: 330; fiscal federalism; intergovernmental relations; grants; fiscal competition; fiscal externalities; decentralization